High neutrophil‐to‐lymphocyte ratio (NLR) is associated with treatment failure and death in patients who have melanoma treated with PD‐1 inhibitor monotherapy. Issue 1 (4th October 2019) - Bartlett, Edmund K.; Flynn, Jessica R.; Panageas, Katherine S.; Ferraro, Richard A.; Sta.Cruz, Jessica M.; Postow, Michael A.; Coit, Daniel G.; Ariyan, Charlotte E.
Abstract : Background: An elevated neutrophil‐to‐lymphocyte ratio (NLR) is associated with poor survival in patients with cancer, including those who receive immunotherapies. The authors sought to investigate NLR as a biomarker of treatment outcomes in patients with melanoma who were treated with PD‐1 inhibition. Methods: Patients undergoing initial treatment with PD‐1 inhibitor monotherapy for stage IV melanoma at a single center from 2012 to 2015 were included. Clinical characteristics and the NLR at baseline and before subsequent treatment cycles were collected. The time to treatment failure (TTF) and overall survival (OS) were evaluated using Kaplan‐Meier and landmark analyses. Results: Among 224 study patients, 63 (28%) had a baseline NLR ≥5. The baseline NLR was significantly associated with Eastern Cooperative Oncology Group performance status and the number of involved metastatic sites. With a median follow‐up of 39 months in survivors, a baseline NLR ≥5 was independently associated with shorter OS (hazard ratio, 2.0; 95% CI, 1.3‐2.9) and TTF (hazard ratio, 1.7; 95% CI, 1.2‐2.4). An NLR increase ≥30% during the first 2 cycles of treatment was associated with worse OS (median, 47 vs 13.5 months; P  < .001) and a trend toward shorter TTF (12.8 vs 5.9 months; P  = .05). A combined baseline NLR ≥5 and an NLR increase ≥30% identified a small cohort with markedly shortened OS (median, 5.8 months) and TTF (median, 1.8 months). Conclusions: Elevated baseline NLR and an increased NLR early during treatment are prognostic for TTF and OS in patients who have melanoma treated with PD‐1 inhibitor monotherapy. Combined, these biomarkers can widely risk‐stratify patients for treatment failure and survival. Abstract : A pretreatment neutrophil‐to‐lymphocyte ratio (NLR) ≥5 and an increase ≥30% in the NLR are independently prognostic for treatment failure and worse overall survival in patients who have melanoma treated with PD‐1 inhibitor monotherapy. The pretreatment NLR is associated with both tumor and host factors, suggesting that the NLR reflects a complex interaction between the tumor and the host immune response.